O (des) caminho até a porta : um estudo sobre o acesso à atenção básica de saúde em três microáreas de Fortaleza - Thé, Marise Cristiane Rocha Lima (2014)
This study examines the accessibility to primary health care services of the population in areas of Fortaleza. Its objectives are to identify accessibility components that influence in the use of these services by the residents of these areas, exploring the reasons for non-accessibility to the health unit, the barriers that hinder the access and the ports of entry in the health care system. It is a descriptive study, quantitative and transversal, carried out in 2013. Were interviewed 247 families. A mapping using Geographic Information System (GIS) that allowed visualization of local health services as well as its relationship with the difficulties and barriers to access sometimes identified by the subjects of this research was done. The results showed 62.3% of these families didn’t view the neighborhood unit as the place of first demand in case of need. The distance and the ease of accessibility to another health center were the main reasons for this. The distance (50.2 %), transportation (45.2 %) and the ignorance about the location and opening hours (21.0 %) were the most frequent difficulties. This research points to the need for a more thorough study of the territory of actuation of the team of the Family Health Program in order to considerer the various barriers that interfere with the accessibility of the population to health services.